Training Decorating Accessories Veil and Family to Increase Revenue and Tourism in Kenagarian Payo Lubuk Sikarah District City of West Sumatra Solok - yasnidawati yasnidawati; Yusmerita Yusmerita; Puji Hujria Suci (Postgraduate School, Universitas Negeri Padang, 2020)
Partners in Service community in Payo Solok District of Lubuk Sikarah are housewives and teenagers drop out of school. The problem faced by the people in the District of Lubuk Sikarah Payo Solok is a lack of knowledge and skills of the communities in the field of fashion, especially in decorating the veil and make accessories. The method used in accordance goals in training. The results of the implementation of the training activities create various accessories that housewives and teenagers (PKK) in Kanagarian Payo Solok, it has the ability and skill in making accessories in various forms by 75%, and the participants have to understand and have base makes a wide range of accessories by 80%. This can be seen from the shape hijab accessories and brooches generated sufficient quality. This is because the participants were seriously and earnestly to follow and activities make hijab accessories. The capacity of the hijab accessories making techniques, participants also have the skill by 85%. Keywords: Hijab Embroidery Training and Accessories